PROBLEMS OF GENDER POLICY IMPLEMENTATION IN THE SECURITY AND DEFENSE SECTOR OF UKRAINE - Сивак, Ольга; Блинников, Георгий; Шевчук, Виктория; Пидгийчук, Светлана (SWorldJournal, 2020)
The analysis of the legal and practical implementation of gender policy in the security and defense sector of Ukraine was conducted with reference to the main conclusions on the implementation of gender policy in 2019 among countries based on the analysis